2007
DOI: 10.1258/135581907779497576
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of self-reported and observational work sampling techniques for measuring time in nursing tasks

Abstract: The self-report work sampling technique is not a reliable method for obtaining an accurate reflection of the work tasks of ward-based nurses. The observational technique was preferred by nurses, and despite concern regarding a potential Hawthorne effect, this was not substantiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
4
23

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(167 citation statements)
references
References 15 publications
5
134
4
23
Order By: Relevance
“…In addition, observed subjects tend to habituate rapidly to being observed. 18 Fifth, since we did not collect identifying data on interns, we were not able to identify associations between intern characteristics and time spent in direct patient care. Sixth, we observed interns during a single month, although time spent with patients may vary throughout the year.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, observed subjects tend to habituate rapidly to being observed. 18 Fifth, since we did not collect identifying data on interns, we were not able to identify associations between intern characteristics and time spent in direct patient care. Sixth, we observed interns during a single month, although time spent with patients may vary throughout the year.…”
Section: Discussionmentioning
confidence: 98%
“…25 Several previous studies in healthcare settings, including RACFs, have suggested that the Hawthorne effect is not significant in direct observation; 6,26,27 consequently, we did not measure it in the present study.…”
Section: Limitationsmentioning
confidence: 89%
“…Discrete sampling of subject's activities is used to build a statistical model of proportions of time (Ampt, Westbrook, Creswick, & Mallock, 2007). …”
Section: Work Samplingmentioning
confidence: 99%